Impressions of 'Newness' in English Canadian Theatre The role of festivals in the consecration and distribution of new work - Ruano, Jessica (University of Ottawa (Canada), 2010)
In English Canadian theatre, there exists a significant divide between established works produced in the mainstream and new work that has traditionally been relegated to the margins of institutional practice. Seeking to bridge this divide are a number of festivals committed to fostering and showcasing plays by Canadian theatre artists and companies and to attracting presenters interested in programming new works for future seasons. In order to succeed in the festival circuit, independent companies must, to a certain extent, cater to the expectations of organizations that value performance that gives the impression of being novel and yet proves accessible to festival audiences and to those targeted by presenters. This plays a role in aesthetics that become characteristic of the companies' work. These aesthetics are not only accepted, but also exploited by festivals that are seeking to legitimize the notion of 'newness', in part, for the purpose of their own sustainability.
Keywords: Theater.